Relationship between Friction Coefficient, Viscosity and Compressibility of Polyethylene Glycol - Kazuaki Hachiya (Japanese Society of Tribologists, 2008)
An ultrasonic liquid processor with the frequency of 20 kHz was used to cleave a principal chain in a polyethylene glycol molecule. The amount of the lubricant molecules cleaved by the ultrasonic disruption was evaluated by the kinematic viscosity measurement. As the kinematic viscosity in the water-glycol hydraulic fluids of the ethylene glycol solutions containing polyethylene glycols decreased monotonously under the condition that the ultrasound of 20 kHz and 40 W was irradiated for one second every five seconds at either 20 or 40 °C, the lubricant molecules could be effectively cleaved while reducing the inter-molecular polymerization. The friction coefficients, ultrasonic velocities, densities, and compressibilities in the water-glycol hydraulic fluids were not influenced by the cleavage process of the lubricant molecules. On the other hand, the kinematic viscosities in the undiluted solutions of ethylene glycol and the polyethylene glycols were proportional to their molecular weights, but the friction coefficients and compressibilities in polyethylene glycols hardly depended on their molecular weights except for those in ethylene glycol. These dependences of the frictional coefficients and compressibilities on the molecular weights resulted from a structure of the lubricant oil film formed on the metal surface.